Desenvolvimento e validação de conteúdo de um protocolo web de autoavaliação da voz de profissionais da voz falada - Martins, Luyênia Kérlia Gomes (2023)
INTRODUCTION: The use of voice in high demand becomes essential for some spoken voice professionals. This fact associated with the characteristics of the environment and working conditions may favor the genesis of Work-Related Voice Disorder (WRVD) and limit the performance of occupational activities. It is necessary to know the reality of these professionals based on specific validated instruments to assess their perspective on their vocal demand in the midst of working conditions. OBJECTIVES: To develop and verify evidence of content validity of a web protocol for self-assessment of the voice of spoken voice professionals METHODS: This is a validation, accuracy and prospective study. It followed the recommendations of the Standards for Educational and Psychological Testing (SEPT), which even describe procedures for obtaining evidence of content-based validity. Initially, a broad review of the literature was carried out with the aim of supporting the researchers in the elaboration of the items and composing the first version of the self-assessment protocol. This version was forwarded and analyzed by the panel of specialists, formed by five speech therapists with expertise in the performance of spoken voice professionals. Later, the individual prior analysis of each judge could be discussed consensually by all, online, using the Delphi method. Based on this consensual analysis, where items were eliminated, combined or adjusted, the researchers structured a second version of the protocol. It was then sent to the judges to analyze remotely, using a form, item by item to extract agreement rates regarding the criteria of relevance, clarity, objectivity and content addressed according to a Likert scale. Based on these analyses, adjustments were made to form a third version. Agreement was measured by Item Content Validity Index (CVI-I) and Content Validity Index (CVI). RESULTS: In its first version, the PAPROvoz consisted of 81 items and ended in its third version with 71 items, with a Likert scale response key, resulting in four marking possibilities, distributed in eight domains related to health and factors of the self. individual, external conditions related to the performance and work environment, voice habits and symptoms, and work activity monitoring measures. All items had the CVI-I at 1.0, except one item resulted in 0.8. The CVI obtained a value of 0.98. Both concordance analysis indices were above the acceptability threshold. CONCLUSION: The PAPROvoz obtained evidence of content validity, it has 71 items, divided into eight domains, response key in Likert scale and all item concordance analysis indices performed by the expert panel obtained acceptable values.